Use and acceptance of video as a strategy to mitigate plagiarism - Laura Alicia Hernández Moreno; Hugo Moreno Reyes; Lizette Berenice González Martínez (Universidad de Guadalajara, 2024)
The present research aimed to determine the use and acceptance of video in the self-creation of assignments or evidence of learning as a strategy to mitigate plagiarism. This research adopted a mixed design, with an experimental, exploratory, and descriptive scope that reflects an innovative approach to meet this challenge. A non-probabilistic sample was considered, comprised of students in their first semester of higher education in the subject of Introduction to Programming at a public university in Mexico. The participants were divided into an intervention group and a control group. The acceptance of the use of the implemented strategy was evaluated using the Technology Acceptance Model and the results revealed the viability and usefulness of the strategy since the students in the intervention group stood out in the creation of their assignments compared to the control group. There was a positive and strong relationship between academic performance and the perceived usefulness of the strategy. We conclude by emphasizing the importance of teachers promoting the active role of students in the development of their work, to promote authentic learning and guarantee educational quality.